2021
DOI: 10.3390/molecules26092747
|View full text |Cite
|
Sign up to set email alerts
|

Valonea Tannin: Tyrosinase Inhibition Activity, Structural Elucidation and Insights into the Inhibition Mechanism

Abstract: Valonea tannin is a natural product readily extracted from acorn shells that has been suggested to have potential skin whitening properties. This study investigated the tyrosinase inhibition activity of extracted valonea tannin and the associated structure–function activity. Nuclear magnetic resonance spectroscopy and molecular weight analysis with gel permeation chromatography revealed that valonea tannin could be characterized as a hydrolysable tannin with galloyl, hexahydroxydiphenoyl and open formed-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Gallic acid, gallotannin, valonia tannin and extracts of plants (e.g., Ceylon olive leaves and pomegranate peel) containing gallic acid exerted antimelanogenic effects directly by acting as a competitive inhibitor of tyrosinase and indirectly by inhibiting tyrosinase via antioxidant actions that affect melanogenesis pathway in vitro and in vivo ( Chen et al, 2009 ; Panich et al, 2013 ; Su et al, 2013 ; Kanlayavattanakul et al, 2020 ; Huang et al, 2021 ; Liu et al, 2021 ). A randomized, double-blind, placebo-controlled clinical trial demonstrated that continuous administration of apple polyphenol rich in procyanidins for 12 weeks improved UV-induced skin pigmentation in heathy women ( Shoji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid, gallotannin, valonia tannin and extracts of plants (e.g., Ceylon olive leaves and pomegranate peel) containing gallic acid exerted antimelanogenic effects directly by acting as a competitive inhibitor of tyrosinase and indirectly by inhibiting tyrosinase via antioxidant actions that affect melanogenesis pathway in vitro and in vivo ( Chen et al, 2009 ; Panich et al, 2013 ; Su et al, 2013 ; Kanlayavattanakul et al, 2020 ; Huang et al, 2021 ; Liu et al, 2021 ). A randomized, double-blind, placebo-controlled clinical trial demonstrated that continuous administration of apple polyphenol rich in procyanidins for 12 weeks improved UV-induced skin pigmentation in heathy women ( Shoji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quercetin glycosides, including hyperoside with IC 50 value of 15.67 µg/mL, are accepted as being suitable for anti-melanogenesis purposes with no cytotoxicity [ 43 ]. Tannic acid exerted tyrosinase inhibition (IC 50 value, 4.0 ± 0.01 mM), this effect was attributed its pyrogallol moiety that played a critical role in the enzyme inhibition process [ 44 ]. In addition, a molecular docking study suggested that the catechol moiety of quercetin might chelate copper in the active site of tyrosinase, causing the blocking of access of l -DOPA into the catalytic center.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies that report this observation for many enzymes such as α-amylase, α-glucosidase, glucoamylase, cholinesterase and tyrosinase [ 38 , 39 , 40 , 41 ]. The mechanism occurring is the formation of stable tannin–protein complexes, which hinder the execution of their enzymatic functions [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%